A balancing act: RNA binding protein HuR/TTP axis in endometriosis patients - Kasra Khalaj (Nature Portfolio, 2017)
Abstract Endometriosis, a major reproductive pathology affecting 8–10% of women is characterized by chronic inflammation and immune dysfunction. Human antigen R (HuR) and Tristetraprolin (TTP) are RNA binding proteins that competitively bind to cytokines involved in inflammation including: tumor necrosis factor alpha (TNF-α), granulocyte macrophage colony stimulating factor (GM-CSF), interleukin 6 (IL-6) among others, and stabilize and destabilize them, respectively. The aim of this study was to examine RNA binding protein (RNABP) HuR/TTP axis in endometriosis patients compared to menstrual stage matched healthy fertile controls in hopes of better understanding their contribution to the pathogenesis of endometriosis. Additionally, using a targeted in vitro siRNA approach, we examined whether knock-down of TTP can play a functional role on other RNABPs that competitively bind to inflammatory targets of TTP in both endometriotic and endometrial epithelial cell lines. Our results suggest that RNABPs TTP and HuR are dysregulated in endometriotic lesions compared to matched eutopic patient samples as well endometrium from healthy controls. Silencing of TTP in endometriotic and endometrial epithelial cells revealed differential response to inflammatory cytokines and other RNABPs. Our results suggest potential involvement of HuR/TTP RNA binding protein axis in regulation of inflammation in endometriosis.